2016
DOI: 10.1186/s13023-016-0416-0
|View full text |Cite
|
Sign up to set email alerts
|

GNAO1 encephalopathy: further delineation of a severe neurodevelopmental syndrome affecting females

Abstract: BackgroundDe novo heterozygous mutations in the GNAO1 gene, encoding the Gα o subunit of G-proteins, are the cause of a severe neurodevelopmental disorder, featuring early infantile seizures, profound cognitive dysfunction and, occasionally, movement disorder (early infantile epileptic encephalopathy-17).MethodsWe report a further case of this association in a 20 month-old Spanish girl with neonatal-onset refractory seizures, progressive microcephaly, oral-lingual dyskinesia and nearly absent psychomotor devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
(34 reference statements)
1
42
0
Order By: Relevance
“…[2][3][4][5]8,10,12,[14][15][16]26 MRI studies have not shown major structural abnormalities in patients with GNAO1 variants. Developmental delay and hypotonia occur in nearly all cases, although they led less frequently to medical attention.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[2][3][4][5]8,10,12,[14][15][16]26 MRI studies have not shown major structural abnormalities in patients with GNAO1 variants. Developmental delay and hypotonia occur in nearly all cases, although they led less frequently to medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] GNAO1 encodes a G-protein α subunit that, along with dimerized β and γ subunits, forms a heterotrimeric G-protein complex. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] GNAO1 encodes a G-protein α subunit that, along with dimerized β and γ subunits, forms a heterotrimeric G-protein complex.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations